Pengaruh Bantuan Iuran JKN Terhadap Pemanfaatan Layanan Antenatal Care di Kabupaten Ogan Ilir, Sumatera Selatan, Indonesia - Munawarah, Siti Halimatul; Ainy, Asmaripa; Chendra, Rudy (LPPM Hang Tuah Pekanbaru, 2025)
Data from the Ogan Ilir District Health Office shows that the coverage of antenatal care services is still not optimal. Only around 60-70% of pregnant women make complete ANC visits (at least four visits during pregnancy) according to the standards set by WHO. Most pregnant women in the Ogan Ilir District enrolled in NHI fall into the Contribution Assistance Recipient (PBI) category. This suggests that contribution assistance is critical in improving access to health services for low-income pregnant women. The purpose of this study was to analyze the effect of JKN contribution assistance on the utilization of Antenatal Care (ANC) services in Ogan Ilir District. The research design was a cross-sectional study using secondary data from the Field Learning Experience by the Faculty of Public Health, Sriwijaya University in 2023. The population was all mothers with children under five, with purposive sampling with 342 respondents in Pemulutan District and Tanjung Batu District, Ogan Ilir Regency, South Sumatra. Univariate analysis was used to describe each variable, and bivariate analysis using Chi-Square Test. The results showed no effect of the variables (NHI contribution assistance, age of father and mother, education of father and mother, number of family members, number of children under five, history of illness, and family income) on ANC service utilization. This indicates the need for additional interventions to increase ANC service utilization in the area.